O retrato do homem negro estereotipado no conto infantil “Boa de garfo”, de Luiz Vilela - Gavioli, Wellerson Clemer dos Santos (2024)
This dissertation focuses on the analysis of the corpus “Boa de Garfo”, by Luiz Vila, based on the categories of analysis: interdiscourse and scenes of enunciation, in light of the theoretical-methodological sport proposed by Dominique Maingueneau (2007, 2008, 2015, 2018). The scenography that is outlined in the literary discourse is contextualized in the period of the Brazilian Republic, after the abolition of slavery, when the currency in force was the cruzeiro, a moment that was marked by much racial discrimination against the black population motivated by the ideological attempt to whiten the population through some political movements, such as the example of immigration to Brazil. The European population that arrived in Brazil overlapped with the black population, which was marginalized, without active participation in the new society on the rise. All this depreciative history fostered the constitution of a structurally racist society, in which racism was accepted and normalized. In the selected corpus, we noticed the voices of the discourse of the myth of “racial democracy” and the reproduction of the image of the black man represented in a stereotypical way. The objectives aim to develop such discourses, as well as to reflect on the importance of positive representation in literary productions, especially for children, in accordance with Law 10.639/03, involving the deconstructing of racist discourses that still persist today. Finally, the results of the announced investigations, which evidence racist discourses that date back to colonial practices in the sense of preaching the superiority of whites over blacks, confirm that there are still many issues to be reviewed, especially in children's stories, so that black children have models from which they can be inspired in the process of constructing their identity